Retracted article: Flexible Fourier Stationary Test in GDP per capita for Central Eastern European Countries - Meng-Nan Zhu (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2011)
Statement of Retraction (http://www.efri.uniri.hr/prikaz.asp?txt_id=7366) This is to notify our respectful reading public that the Editorial Board of the journal Zbornik radova Ekonomskog fakulteta u Rijeci, časopis za ekonomsku teoriju i praksu/ Proceedings of Rijeka Faculty of Economics, Journal of Economics and Business has retracted the following article from publication: “Flexible Fourier Stationary Test in GDP per capita for Central Eastern European Countries“, by Hsu-Ling Chang, Chi-Wei Su, Meng-Nan Zhu, published in our journal Zbornik radova Ekonomskog fakulteta u Rijeci, časopis za ekonomsku teoriju i praksu/ Proceedings of Rijeka Faculty of Economics, Journal of Economics and Business, 2011, vol. 29 (1), pp. 51-63 and almost concurrently published in the journal Eastern European Economics, 2011, vol. 49 (3), pp. 54-65. Being in contact with Josef C Brada, Professor Emeritus, Editor of the journal Eastern European Economics (EEE), we realized that the paper had been sent to both journals, although first published in the EEE and then in our Journal. According to professor Brada’s and our analysis, the paper published in these two journals is exactly the same, except for minor differences in wording, most likely due to editing the text before publication. The outstanding differences are in the title and the fact that the paper published in our Journal has three authors and in EEE journal has two. Whatsoever, owing to the fact that the article had been sent to both journals almost at the same time, it had been impossible to find out the case during the review procedure. Due to this unpleasant situation, our Editorial Board would like to inform our valuable readers that all the necessary measures to retract the paper from our publication have been undertaken and according to publishing ethical principles, cooperation with the authors of the retracted paper have been stopped. Although, in this case neither EEE nor our Journal had any chance to envisage and prevent this double publication in time, we do ask our readers to accept our deepest apology. Ivo Sever, PhD Editor- in- Chief